2019
DOI: 10.1177/0002039719848513
|View full text |Cite
|
Sign up to set email alerts
|

Where Regional Norms Matter: Contestation and the Domestic Impact of the African Charter on Democracy, Elections and Governance

Abstract: Twelve years after the adoption of the African Charter on Democracy, Elections and Governance, scholars and policymakers are still pondering whether the regional document has had any actual effect. Based on case studies from Madagascar and Burkina Faso, this article demonstrates the Charter’s impact on political dynamics within both countries. By analysing contestations around the application of Article 25(4), which defines who is eligible to run in transitional elections, I show that various national and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Nevertheless, our inquiry also revealed that the implementation of the ACDEG remains limited and varies significantly depending on the democratic quality of the implementing governmental regime (Engel, 2019) as well as on the respective policy issue (Abdulmelik and Bellay, 2019;Witt, 2019b). Accordingly, the core objective of the Special Focus was to interrogate the different contextual factors that shape the nature, dynamics, and scope of the implementation of ACDEG.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, our inquiry also revealed that the implementation of the ACDEG remains limited and varies significantly depending on the democratic quality of the implementing governmental regime (Engel, 2019) as well as on the respective policy issue (Abdulmelik and Bellay, 2019;Witt, 2019b). Accordingly, the core objective of the Special Focus was to interrogate the different contextual factors that shape the nature, dynamics, and scope of the implementation of ACDEG.…”
Section: Resultsmentioning
confidence: 90%
“…This Special Focus further demonstrates that although, from a strict legal perspective, the ACDEG's jurisdiction is territorially limited since only thirty-four countries out of the fifty-five AU member states have ratified the treaty, its impact has been felt beyond its State Parties. This includes, for example, its application by the PSC following the coup in Madagascar even though the latter was not yet a State Party to the treaty at the time (Witt, 2019b) or as a key benchmark during AU electoral observation missions (Abdulmelik and Bellay, 2019) or as the main catalyst to improve continental coordination and policymaking in the domain of democratic governance among different AU institutions through the AGA (Engel, 2019). We anticipate that the influence of the Charter will continue to grow as the most important democratic governance instrument in Africa, not only because the African Court on Human and Peoples' Rights decided to recognise the Charter as a justiciable legal instrument (Kioko, 2019;Niyungeko, 2019), but also because of its growing political authority.…”
Section: Resultsmentioning
confidence: 99%
“…This, too, is an effect of African regional interventions that has hitherto rarely been accounted for. If regional norms and institutions had been seen as impotent und irrelevant, they would not have been debated publicly or used for political purposes (see also Witt 2019).…”
Section: Resultsmentioning
confidence: 99%
“…While some welcomed regional law because of their own interests, others rejected it on similar grounds as well. The debate sparked by the ECOWAS Court's decision thus highlights how regional organizations and their norms, rather than being perceived passively by local audiences, become subject to local elites' struggle to make sense of what is going (wr)on(g) and to exert their own role in times of transition (see also Witt 2019).…”
Section: Burkina Faso: Contesting Regional Intervention In Times Of Pmentioning
confidence: 99%
“…Studies show that the AU norms and decision-making structures influence political dynamics within African countries (Witt 2019), shape African international relations (Karbo & Murithi 2018; Tieku 2018 a ), and even impact the politics of other regions (Souaré 2018). Hardt has persuasively argued that AU member states delegate to the AUC even in sovereignty-sensitive areas such as peace operations (Hardt 2016: 179).…”
Section: Introductionmentioning
confidence: 99%